If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -12 = 7x + -48 Reorder the terms: -12 + 5x = 7x + -48 Reorder the terms: -12 + 5x = -48 + 7x Solving -12 + 5x = -48 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -12 + 5x + -7x = -48 + 7x + -7x Combine like terms: 5x + -7x = -2x -12 + -2x = -48 + 7x + -7x Combine like terms: 7x + -7x = 0 -12 + -2x = -48 + 0 -12 + -2x = -48 Add '12' to each side of the equation. -12 + 12 + -2x = -48 + 12 Combine like terms: -12 + 12 = 0 0 + -2x = -48 + 12 -2x = -48 + 12 Combine like terms: -48 + 12 = -36 -2x = -36 Divide each side by '-2'. x = 18 Simplifying x = 18
| -8x^5+0x^4+7x^3+2x^2-5x-9=0 | | -3/7x-14=7 | | -6x-8(1+7x)=-8 | | -8x^5+0x^4+7x^3+2x^2-5x-9=3 | | 4/3x-2=2x | | 5e^3x=8e^2x | | 275=-x-9(9-10x) | | 24(p+35)=888 | | 25=-5-2x | | -16=d+-21 | | 9.2(x-19)=132.48 | | 7+3x-2x=-4 | | Y-4=-1/4(x-5) | | 7m-26=2 | | 7/9x-2=5/6 | | -8(8+3x)+3=155 | | 2y/3-y/6=1/2 | | -16=d+213 | | 3(7x+6)=9x-2 | | (3/7)•2= | | -8x^5+0x^4+7x^3+2x^2-5x-9=-211 | | 17x+14y+145=0 | | -5-3(-10r+2)=499 | | 11x+12-8x=30-3x | | 136=8+8n | | f(x)=7x^2-5x^3 | | 10log(x)=-8 | | -2(3x+10)=5x-6 | | 178-b=92 | | 7+3x+(-2x)=4 | | 9+2x=11x | | 6+d=2d+1 |